2018
DOI: 10.3389/fnagi.2018.00139
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MicroRNAs-Mediated Autophagic Flux: A New Regulatory Avenue for Neurodegenerative Diseases With Focus on Prion Diseases

Abstract: Prion diseases are fatal neurological disorders affecting various mammalian species including humans. Lack of proper diagnostic tools and non-availability of therapeutic remedies are hindering the control strategies for prion diseases. MicroRNAs (miRNAs) are abundant endogenous short non-coding essential RNA molecules that negatively regulate the target genes after transcription. Several biological processes depend on miRNAs, and altered profiles of these miRNAs are potential biomarkers for various neurodegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 162 publications
(222 reference statements)
0
22
0
Order By: Relevance
“…(B) Structural features of the miRNA-146a encoding DNA locus at chromosome 5q33.3 and details of the NF-κB-sensitive miRNA146a gene showing three upstream (5 ′ ) canonical regulatory NF-κB binding sites; as might be expected, miRNA-146a transcription is highly sensitive to induction by NF-κB (2,3,14,15,20,21); (C) pre-miRNA-146a transcribed from the miRNA-146a locus has the intrinsic potential to form an extremely stable 35-base-pair stem, 60-nucleotide loop sncRNA structure (stem-loop E A = −49.5 kcal/mol) with miRNA-146a encoded in the distal loop; several other secondary structures of alternate miRNA-146a-stem-loop containing configurations are possible and the 5 ′ and 3 ′ ends of pre-miRNA-146a may be significantly extended; in all other high-stability precursor miRNA-146a models, the stem-loop structure containing the mature miRNA-146a sequence is consistently located in the very distal end of the predicted loop [DNA sequence shown; upper case; highlighted in yellow and delineated by arrows on the left side of (C)]; RNA-polymerase II-based transcription and processing by Dicer (RNase III) of the miRNA-146a-5p precursor (pre-miRNA-146a-5p) generated by this unique stem-loop structure yields a mature miRNA-146a-5p [miRNA-146a-5p sequence over-lined with a yellow bar in sequence of their proximal promoter regulatory regions (9-12) (Figure 1). One of these miRNAs is miRNA-146a, normally only moderately abundant in the human brain neocortex and hippocampus, but inducible to many times its basal level by pathogenic agents associated with stress, pro-inflammatory glycolipids (such as LPS), local levels of reactive oxygen species (ROS), and the abundance of Aβ42 peptides and prion amyloids whose accumulation are characteristic, respectively, of the human disorders Alzheimer's disease (AD) and prion disease (PrD) (11,12,14,(24)(25)(26)(27)(28)(29)(30)(31)(32). For example, in one study, Genechip-and microfluidic fluorescent array-based and/or LED-Northern dot blot miRNA analysis that interrogates the entire 2,650 miRNAs yet characterized in human brain tissues revealed a selective upregulation of miRNA-146a in 36/36 short post-mortem interval (PMI) human superior temporal lobe neocortical tissue specimens analyzed, compared to 30-age-, gender-, and PMImatched controls (all PMIs < 3.1 h) (10-12, 14, 24, 25).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Structural features of the miRNA-146a encoding DNA locus at chromosome 5q33.3 and details of the NF-κB-sensitive miRNA146a gene showing three upstream (5 ′ ) canonical regulatory NF-κB binding sites; as might be expected, miRNA-146a transcription is highly sensitive to induction by NF-κB (2,3,14,15,20,21); (C) pre-miRNA-146a transcribed from the miRNA-146a locus has the intrinsic potential to form an extremely stable 35-base-pair stem, 60-nucleotide loop sncRNA structure (stem-loop E A = −49.5 kcal/mol) with miRNA-146a encoded in the distal loop; several other secondary structures of alternate miRNA-146a-stem-loop containing configurations are possible and the 5 ′ and 3 ′ ends of pre-miRNA-146a may be significantly extended; in all other high-stability precursor miRNA-146a models, the stem-loop structure containing the mature miRNA-146a sequence is consistently located in the very distal end of the predicted loop [DNA sequence shown; upper case; highlighted in yellow and delineated by arrows on the left side of (C)]; RNA-polymerase II-based transcription and processing by Dicer (RNase III) of the miRNA-146a-5p precursor (pre-miRNA-146a-5p) generated by this unique stem-loop structure yields a mature miRNA-146a-5p [miRNA-146a-5p sequence over-lined with a yellow bar in sequence of their proximal promoter regulatory regions (9-12) (Figure 1). One of these miRNAs is miRNA-146a, normally only moderately abundant in the human brain neocortex and hippocampus, but inducible to many times its basal level by pathogenic agents associated with stress, pro-inflammatory glycolipids (such as LPS), local levels of reactive oxygen species (ROS), and the abundance of Aβ42 peptides and prion amyloids whose accumulation are characteristic, respectively, of the human disorders Alzheimer's disease (AD) and prion disease (PrD) (11,12,14,(24)(25)(26)(27)(28)(29)(30)(31)(32). For example, in one study, Genechip-and microfluidic fluorescent array-based and/or LED-Northern dot blot miRNA analysis that interrogates the entire 2,650 miRNAs yet characterized in human brain tissues revealed a selective upregulation of miRNA-146a in 36/36 short post-mortem interval (PMI) human superior temporal lobe neocortical tissue specimens analyzed, compared to 30-age-, gender-, and PMImatched controls (all PMIs < 3.1 h) (10-12, 14, 24, 25).…”
Section: Overviewmentioning
confidence: 99%
“…Interestingly, as is further discussed below, there is what appears to be a strong microglial cell-mediated inflammatory and immunological component to both AD and PrD. It has been suggested that miRNA-146a may be both fundamental and integral to innate-immune or inflammatory brain cell responses in AD and PrD-mediated infections, and in other terminal neurological disorders that involve (i) the progressive and irreversible inflammatory neurodegeneration of both diseased murine and human brain tissues and cells; (ii) end-stage proteolipid accumulation; and (iii) the many altered neurochemical and neuropathological signaling processes associated with them (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Overviewmentioning
confidence: 99%
“…It is noteworthy that several miRNAs have been identified to be associated with prion-infected exosomes, some of which are identifiable in body fluids, presenting potential as biomarkers for prion disease [ 88 , 126 , 127 , 128 ].…”
Section: Cellular Trafficking In Prp Sc Infectimentioning
confidence: 99%
“…Since SOD1 is regulated by transcription factors, such as NFκB (Milani et al, 2011), which in turn are controlled by environmental stimuli, investigating the mechanism behind increased SOD1 levels might yield better understanding on mechanisms of astrocyte-mediated neurotoxicity. Since autophagy can be regulated via microRNAs (Shah et al, 2018), investigating whether microRNAs secreted by C9-HRE astrocytes are the underlying mechanism of the inhibition of autophagy initiation in co-cultured cells would be interesting in order to find therapeutic targets.…”
Section: Astrocytes In Model Systems Of C9-ftld and C9-alsmentioning
confidence: 99%